2020
DOI: 10.21865/ridep56.3.09
|View full text |Cite
|
Sign up to set email alerts
|

Evidencias de Validez Convergente y de Criterio del Maternal Behavior Q-Sort (MBQS) 3.1 en Madres Peruanas

Abstract: El presente estudio presenta evidencias de validez convergente del MBQS 3.1 con la versión 2.1 y de validez de criterio con el Attachment Q-Sort (AQS). La muestra estuvo conformada por 27 madres peruanas con hijos de ocho a once meses de edad y de nivel socioeconómico bajo de Lima. La edad promedio fue de 27.96 años (DE=6.02) y la mayoría reportó estudios secundarios (63%). Se encontró una fuerte y positiva asociación entre las versiones 2.1 y 3.1 (r=.76, p<.01). Los perfiles de conducta materna del MBQS 3.1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(84 reference statements)
0
3
0
1
Order By: Relevance
“…In this respect, the Maternal and Paternal Parenting Styles Scale (PSS-MP), consisting of six factors, was validated in Chilean population (Gálvez et al, 2021). Likewise, in Peru, a study reported the convergent validity of the Maternal Behavior Q-Sort (MBQS), which comprises three factors and 90 questions ( Bárrig-Jó et al, 2020 ). Another of the scales validated in the Peruvian population is the Parental Behavior Scale (PBS), composed of eight factors and 45questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the Maternal and Paternal Parenting Styles Scale (PSS-MP), consisting of six factors, was validated in Chilean population (Gálvez et al, 2021). Likewise, in Peru, a study reported the convergent validity of the Maternal Behavior Q-Sort (MBQS), which comprises three factors and 90 questions ( Bárrig-Jó et al, 2020 ). Another of the scales validated in the Peruvian population is the Parental Behavior Scale (PBS), composed of eight factors and 45questions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a research work to validate the Maternal Behavior Q-Sort (MBQS) scale, containing three factors and 90 questions, was also reported in Peru ( Bárrig-Jó et al, 2020 ). Finally, another paper addressed the validation of the Parental Behavior Scale (PBS), consisting of eight factors and 45 questions ( Manrique-Millones et al, 2014 ), which was applied to a sample of 591 parents of children in sixth grade of primary education in this country.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity was assessed with seven different instruments, of which the Adult Sensitivity Scale (E.S.A; Santelices et al, 2012) is the only one that has been developed in Latin America, and has been shown to have adequate validity and reliability for its use in different contexts in Chile (Santelices et al, 2012). Additionally, the maternal Qsorts are the only ones with psychometric studies in Latin American samples (Bárrig-Jó et al, 2020;Díaz & Nóblega 2020;Salinas-Quiroz et al, 2014). Almost all of the publications using other instruments presented here did report information about the measures they used for their specific samples, and described their training processes, along with information about the achieved intercoder reliability at training or when coding, which was adequate in all cases.…”
Section: 22mentioning
confidence: 99%
“…En contraste, los avances científicos en desarrollo infantil, han acumulado evidencia empírica desde la teoría del apego, con aportes sustanciales para la construcción de políticas que propenden por garantizar a los niños el pleno ejercicio de sus derechos. Desde este último marco teórico se ha aportado información valiosa para la comprensión del desarrollo afectivo, social y cognitivo de los niños en contextos como la familia y la escuela (Salinas y Posada, 2014;Salinas, 2015;Santelices et al,, 2015;Araujo et al, 2015;Berlinski & Schady, 2015;Farmer et al, 2011;McGrath & Bergen, 2015;Hamre et al, 2014;Jamilet et al, 2015;Williford et al, 2013;Carbonell et al, 2014;Duque-Romero, 2020;Bárrig-Jó et al, 2020;Salinas-Quiroz et al, 2020).…”
Section: Palabras Clavesunclassified